PERANCANGAN SISTEM INFORMASI BERBASIS WEBSITE PEMBUATAN SURAT PERNYATAAN AHLI WARIS - Dewi Yuliyati; Dwi Budi Santoso; Mariana, Novita (Jurnal Informatika, 2026)
Abstract —  Public administrative services require procedures that are fast, accurate, transparent, and easy to access. One service with a relatively complex administrative flow at Gayamsari Sub-district is the issuance of a Certificate of Heir Statement (Surat Pernyataan Ahli Waris/SPAW). Field observations show that the manual service process causes queues, repeated visits due to incomplete files, document verification delays, and risks of administrative data errors. This study aims to design and build a web-based information system to support SPAW services in a more structured and accountable manner. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall model, covering requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and literature study. The application was implemented using HTML, CSS, JavaScript, PHP, and MySQL. The results indicate that the system enables citizens to submit applications online, upload required documents, monitor application status, and receive clearer service information. For officers, the system supports data management, document verification, and notification of new applications. Functional testing using Black Box Testing shows that the main features run according to the designed requirements, making the system feasible as a digital support tool for SPAW services at Gayamsari Sub-district.   Key word — Public Service, Information System, Certificate of Heir Statement, Website, SDLC.